Impact of Product Quality, Price, and Promotional Activities on Consumer’s Purchase Decision on a Non-Subsidized NPK Fertilizer Market Leading Brand: Purchase Interest as a Mediator - Ronny Hansje Walean; Deny Indra Pratama (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study investigates the influence of product quality, price, and promotional activities on the choices made while purchasing a market leading, non-subsidized NPK fertilizer brand in Indonesia. There is less study on agricultural marketing before this research. The study specifically looks at how purchase interest plays a role in mediating these factors. A total of 231 customers participated in an online survey, and the data obtained were evaluated using the SmartPLS software. The results indicate that the quality and price of a product have a substantial impact on the level of interest in making a purchase, which subsequently has a considerable influence on the final choice to make the buy. Curiously, there is a direct relationship between pricing and the level of interest in making a purchase. This emphasizes that this market leading NPK fertilizer brand is perceived as a product of great worth by the buyer. However, promotional activities have a minimal impact on the choice to purchase and only a weak connection with the level of interest in buying. The findings highlight the significance of purchase interest as a crucial element in the consumer's journey towards making a purchase, surpassing the impact of promotional tactics employed by leading fertilizer brands in the market. The study offers significant insights for manufacturers and policymakers in Indonesia, emphasizing the importance of prioritizing product quality and pricing strategies to improve customer interest and stimulate purchasing decisions.